Organizing Committee - Chien, Steve; Do, Minh; Fern, Alan; Ruml, Wheeler (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
List of organizing committee members for the Twenty-Fourth International Conference on Automated Planning and Scheduling.